Genetic and Expression Analyses of the 'Nkrp1-Clr' Gene Cluster - Zhang, Qiang (Université d'Ottawa / University of Ottawa, 2012)
Natural killer (NK) cells, lymphocytes of the innate immune system, can recognize a wide array of cells via several receptors families such as Ly49 and NKR-P1. The Nkrp1 gene family encode for C-type lectin-like receptors which can recognize their ligands, Clr, on target cells. Nkrp1 and Clr genes are intertwined in the NK gene complex and are thus inherited together. The Nkrp1-Clr genes in 129S6 and BALB/c mouse strains show significant sequence polymorphism compared to those of C57BL/6 mice while the overall gene organization and gene number are conserved. RT-PCR was utilized to study the expression of individual Nkrp1-Clr genes. In situ hybridization was performed to validate expression results from RT-PCR, as well as to verify the cell types in which Nkrp1-Clr genes are expressed. Surprisingly, our expression studies reveal an interesting pattern of expression of Nkrp1 and Clr genes not only in lymphoid tissues but also in the epithelial cells of the intestine, kidney, eye and lung, the myocytes of the heart and skeletal muscle, and possibly some endothelial cells, indicating novel functions of NK cells in these tissues.
Keywords: Nkrp1; Clr; In situ hybridization; natural killer cell